2020
DOI: 10.14202/vetworld.2020.586-592
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of graded level of Silkworm pupae (Bombyx mori) oil on methane production, fermentation characteristics, and protozoal populations

Abstract: Aim: The present study was undertaken to evaluate the effect of variable levels of silkworm pupae oil and roughage: concentrate ratio on in vitro methane production, fermentation characteristics, and rumen protozoa population. Materials and Methods: In vitro gas production study (24 h) was performed with graded levels of silkworm pupae oil, namely, 0.5, 1, 2, 4, and 5% of the basal diet and four variable dietary regimes consisting roughage and concentrate in different proportions (70:30, 60:40, 50:50,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
2
0
0
Order By: Relevance
“…Despite an unexpected increase in ammonia concentration and protozoa population counts in rumen fluid, H. illucens oil decreased methanogenesis in a dose-dependent manner, with significant effects with inclusion levels equal or higher than 4%. The same general trend was also reported by Thirumalaisamy et al (2020) , using increasing levels of B. mori oil (0.5–5% diet), and in a previous study by Jayanegara et al (2020) , who tested the in vitro effects of the addition of 5% of insect oils with different unsaturation degree (species of origin are reported in Table 1 ). Interestingly, Thirumalaisamy et al (2020) showed stronger antimethanogenic effects in high-forage substrates, whereas Jayanegara et al (2020) reported no interaction between effect of insect oil and basal diet composition (70:30 or 30:70 F:C ratio) on enteric methane production.…”
Section: Insects As a Source Of Lipidssupporting
confidence: 83%
See 1 more Smart Citation
“…Despite an unexpected increase in ammonia concentration and protozoa population counts in rumen fluid, H. illucens oil decreased methanogenesis in a dose-dependent manner, with significant effects with inclusion levels equal or higher than 4%. The same general trend was also reported by Thirumalaisamy et al (2020) , using increasing levels of B. mori oil (0.5–5% diet), and in a previous study by Jayanegara et al (2020) , who tested the in vitro effects of the addition of 5% of insect oils with different unsaturation degree (species of origin are reported in Table 1 ). Interestingly, Thirumalaisamy et al (2020) showed stronger antimethanogenic effects in high-forage substrates, whereas Jayanegara et al (2020) reported no interaction between effect of insect oil and basal diet composition (70:30 or 30:70 F:C ratio) on enteric methane production.…”
Section: Insects As a Source Of Lipidssupporting
confidence: 83%
“…The same general trend was also reported by Thirumalaisamy et al (2020) , using increasing levels of B. mori oil (0.5–5% diet), and in a previous study by Jayanegara et al (2020) , who tested the in vitro effects of the addition of 5% of insect oils with different unsaturation degree (species of origin are reported in Table 1 ). Interestingly, Thirumalaisamy et al (2020) showed stronger antimethanogenic effects in high-forage substrates, whereas Jayanegara et al (2020) reported no interaction between effect of insect oil and basal diet composition (70:30 or 30:70 F:C ratio) on enteric methane production. Overall, these studies suggest a promising potential to alleviate this energy loss and decrease the environmental impact of livestock.…”
Section: Insects As a Source Of Lipidssupporting
confidence: 83%